Optimización del proceso de purificado de agua envasada en nueva cascada gsm. En la ciudad de Puyo mediante un estudio de tiempos - Mena Urresta, Rober Jholaus (2022)
“Nueva Cascada GSM” is a microenterprise dedicated to water purification and packaging in 20-liter drums, despite its short history it has been very well received in the market, however, the continuous improvement must be constant facing the competition, since, it is important to have a time study in the production process, therefore, this research project is focused on it in order to determine the activities carried out and unnecessary distances in the areas that require analysis to propose an improvement plan. A check list, general flowchart, travel diagram, analytical flowchart must be identified to obtain information on the production of bottled water purifying process which will be focused on a time study. The number of observations, basic time, supplements, standard time and production capacity will be calculated to determine the current production of the plant, an improvement plan will be developed which consists of unifying areas and activities, eliminating unproductive time and redesigning the plant to obtain an increase in production, a good distribution of the plant and improve profits. Finally, it is reflected that the time study meets all its objectives and in turn optimizes the production process of water purification resulting in an increase of 13 drums per day, generating a profit of $ 19.50 per day and an increase of 23% in its production in relation to the current process.